Membuat Aplikasi Pelestarian dan Pengenalan Tokoh Wayang di berbagai Daerah di Indonesia Berbasis Android (Information Technology and Telematics, 2014)
ABSTRACTIndonesia is known to have diverse cultures , one existing culture centuries ago is the puppet arts . Along the development era , this art gradually neglected . Creating recognition and preservation applications puppet in various regions in Indonesia is an android -based goals puppet to preserve endangered culture on young people and the general public to better recognize , preserve and understand the history of the puppets in their respective areas through mobile media or smartphone . The method used to create or develop software this is a prototype model . This method is a method in which the results of the analysis of the development of the system per section directly incorporated into a model of the entire system without having to wait for complete analysis. The program has several layouts and activity , including initial display page (main activity ) , the layout of the history tab (menu activity ) , page layouts puppet area ( menu activity ), contents page layout puppet areas ( activity ) and layout to display images ( grid activity ) , the project file is named puppet extension apk.Keywords:Puppet,Android